Dhikr Relaxation Training in Pregnant Women Classes In Purbosari Posyandu Purbayan Village - Wahyuni, Endang Sri; Mahmudah, Irvina Nurul; Rahmawati, Ai; Handayani, Juleha Duwi; Wardani, Anindya Kusuma; Cahyani, Renata Fina Antika (Universitas Muhammadiyah Surakarta, 2023)
Pregnancy is a vulnerable period with psychological disturbances in the mother. Anxiety can arise due to worries about the pregnancy and the fetus it contains. Especially when the Covid-19 pandemic emerged, causing anxiety for pregnant women, especially the fear of being infected with Covid-19. The aim of PKM (community service) activities is to improve skills in performing dhikr relaxation techniques in pregnant women. Method of Implementation: The partner for this PKM activity is the class of pregnant women at Posyandu Purbosari in Purbayan Village, Sukoharjo district. It is carried out by holding training using lecture and discussion methods, simulations and demonstrations. Then the pregnant women are accompanied to practice dhikr relaxation technique skills. The training conducted has been able to increase the ability of pregnant women to relax dhikr by 100%. The average anxiety level of pregnant women measured by the HARS scale is a score of eight, meaning that pregnant women are in the mild anxiety category. Based on the interview results, the majority of pregnant women said they felt calmer and more relaxed after doing dhikr relaxation exercises. Pregnant women are committed to continuing the practice independently using the dhikr relaxation guide video at their respective homes. Conclusion: Pregnant women are able to practice the dhikr relaxation method taught, feel more relaxed and calm after doing the training. The results of the evaluation in the last week showed that mothers were able to do dhikr relaxation exercises independently at their respective homes using the video guide provided.